Relationship of music to mood, experience value and behavioral intentions during exercise / Azrina Md Azhari - Md Azhari, Azrina (2011)
The aim of this study was to examine the relationship of music to the mood, experience value and behavioural intentions during exercise. Which means this study want to discover is there any relationship when exercise with music to the positive mood, positive experience value and behavioural intentions during exercise. 200 questionnaires were distributed to the respondents. Basically, by the result from the collected questionnaires, the output results confirms that there is a significant positive relationship exists between mood, experience value and behavioural intentions (r = 0.716, p < 0.05). Therefore, respondent's mood and experience value are associated with higher behavioural intention when exercise with music. Based on the finding, the conclusions were formulated where the positive mood and positive experience value that experienced by the respondents during exercise with music also influences the behavioural intentions of the respondents. So that, to gain a positive influence to the mood, experience value and behavioural intention during exercise, each people should have an exercise with music or join the aerobic dance classes.